A história local de Santana da Boa Vista: perspectivas e possibilidades de integração platina - Augustin, Roberta Lopes (2002)
Rio Grande do Sul is had as one of States, developed, presenting indicators socioeconomic superiors to the remaining of the country. Although it is placed in a better position, it is not a homogeneous State. Following this reasoning the objective of this work went analyze the historical process of the municipal district of Santana from Boa Vista, while personal computerhistory, using fundamentally the method of oral history. To the we rescue the oral memory of the santanenses, we detected the situation of socioeconomic penury of the municipal district, relating the cultural subject of Santana from Boa Vista, having been a paradox, during its history, stimulating factor or limit for its growth. The bravery culture took to the decline of the area in I swell it of its conservation for the local society, that didn't get to diversify and to adapt to the new conjunctures. The indicators that today present the sub development" situation they are, in a lot, consequence of that culture, and, dialect, that culture comes as a consequence of the own process of formation of that municipal district. The study detected, that for we understand the cultural identity it is necessary to involve the theme as a whole, as well as to consider all the particularizes that it composes it. Only on that moment that can analyze a cultural identity in a certain place, sub-area, area, country and even continent.